Unique Exercise Lactate Profile in Muscle Phosphofructokinase Deficiency (Tarui Disease); Difference Compared with McArdle Disease - Piirilä, Päivi; Similä, Minna E.; Palmio, Johanna; Wuorimaa, Tomi; Ylikallio, Emil; Sandell, Satu; Haapalahti, Petri; Uotila, Lasse; Tyynismaa, Henna; Udd, Bjarne; Auranen, Mari (Frontiers in Neurology, 2016)
Introduction Glycogen storage disease V (GSDV, McArdle disease) and GSDVII (Tarui disease) are the most common of the rare disorders of glycogen metabolism. Both are associated with low lactate levels on exercise. Our aim was to find out whether lactate response associated with exercise testing could distinguish between these disorders. Methods Two siblings with Tarui disease, two patients with McArdle disease and eight healthy controls were tested on spiroergometric exercise tests with follow-up of venous lactate and ammonia. Results A late increase of lactate about three times the basal level was seen 10–30 min after exercise in patients with Tarui disease being higher than in McArdle disease and lower than in the controls. Ammonia was increased in Tarui disease. Discussion Our results suggest that follow-up of lactate associated with exercise testing can be utilized in diagnostics to distinguish between different GSD diseases.